A Novel Power Factor Correction Modified Bridge Less-CUK Converter for LED Lamp Applications - Saravanan D; Gopinath M (Institute of Advanced Engineering and Science, 2016)
In recent decades, several research works have been focused on the efficient Power Factor Correction (PFC) converter design in to meet the power supply efficiency. Conventional PFC cuk converter widely uses the full bridge rectifier which had resulted in overall increase of converter losses and inefficiency. This paper is intended to develop a novel PFC Bridgeless cuk converter for LED lamp applications. In this work, the limitations of the conventional PFC Cuk converter are resolved. The major contributions of the proposed work include the minimization in the number of conduction devices and minimization of the power utility devices which in turn resulted in minimal losses and better efficiency. Moreover, the proposed converter works in DCM which requires only one voltage sensor which results in reduced cost. The proposed Modified BL Cuk converter (MBL-CUK) for LED lamp is simulated in MATLAB and the corresponding results show the better power quality indices such as power factor and Total Harmonic Distortion.